Antenatal Diagnosis of Ambiguous Genitalia in a Fetus at 28th Gestational Week - Ayhan Coşkun; Özgür Özdemir; Gülcan Akdemir; Gürkan Kırank (Medical Network, 2007)
To discuss an ambiguous genitalia case diagnosed antenatally. A fetus with ambiguous genitalia has been determined during US scan performed during 28th gestational week and confirmed with physical exam postnatally. External genitalia evaluation should be a part of routine anomaly screening as ambiguous genitalia can be life threatening issue especially in enzyme defects according to the deficient enzyme type